Ben Sira’s View of Women : A Literary Analysis - Trenchard, Warren C. (Warren Charles) (Book collections on Project MUSE., 2020)
An "analysis of gender not only in the biblical (Apocrypha) book of Sirach but in literature from the Second Temple period more broadly. Trenchard's study remains important for thinking about "misogyny" in the ancient world, in all of its literary as well as cultural dimensions."--Publishers' preface